Patient characteristics associated with risk of first hospital admission and readmission for acute exacerbation of chronic obstructive pulmonary disease (COPD) following primary care COPD diagnosis: a cohort study using linked electronic patient records. Issue 1 (22nd January 2016) - Hunter, L C; Lee, R J; Butcher, I; Weir, C J; Fischbacher, C M; McAllister, D; Wild, S H; Hewitt, N; Hardie, R M
Abstract : Objectives: To investigate patient characteristics of an unselected primary care population associated with risk of first hospital admission and readmission for acute exacerbation of chronic obstructive pulmonary disease (AECOPD). Design: Retrospective open cohort using pseudonymised electronic primary care data linked to secondary care data. Setting: Primary care; Lothian (population approximately 800 000), Scotland. Participants: Data from 7002 patients from 72 general practices with a COPD diagnosis date between 2000 and 2008 recorded in their primary care record. Patients were followed up until 2010, death or they left a participating practice. Main outcome measures: First and subsequent admissions for AECOPD (International Classification of Diseases (ICD) 10 codes J44.0, J44.1 in any diagnostic position) after COPD diagnosis in primary care. Results: 1756 (25%) patients had at least 1 AECOPD admission; 794 (11%) had at least 1 readmission and the risk of readmission increased with each admission. Older age at diagnosis, more severe COPD, low body mass index (BMI), current smoking, increasing deprivation, COPD admissions and interventions for COPD prior to diagnosis in primary care, and comorbidities were associated with higher risk of first AECOPD admission in an adjusted Cox proportional hazards regression model. More severe COPD and COPD admission prior to primary care diagnosis were associated with increased risk of AECOPD readmission in an adjusted Prentice-Williams-Peterson model. High BMI was associated with a lower risk of first AECOPD admission and readmission. Conclusions: Several patient characteristics were associated with first AECOPD admission in a primary care cohort of people with COPD but fewer were associated with readmission. Prompt diagnosis in primary care may reduce the risk of AECOPD admission and readmission. The study highlights the important role of primary care in preventing or delaying a first AECOPD admission.